2005
DOI: 10.1177/08857288050280010701
|View full text |Cite
|
Sign up to set email alerts
|

Mandates and Effective Transition Planning Practices Reflected in IEPs

Abstract: In this study, the researchers analyzed the transition components of 399 Individualized Education Programs (IEPs). In many cases, transition goal areas mandated by the 1997 amendments to the Individuals with Disabilities Education Act (IDEA) either were not addressed or were inadequately detailed. Effective practices, such as career planning and self-determination enhancement, were not incorporated within most plans, and the study indicated that students frequently were solely responsible for carrying out acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
72
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 147 publications
(77 citation statements)
references
References 18 publications
4
72
0
1
Order By: Relevance
“…The surveys were developed to measure the experiences and expectations of youth with disabilities as they transition to adulthood. Based on previous research (Powers et al, 2005), the following themes were identified: postschool activities cited in the IDEA (i.e., independent living, community participation, postsecondary education), self-determination skills, barriers and sources of support for transition, and gender equity. Multiple items for each of these themes were developed.…”
Section: Instrumentation and Data Analysismentioning
confidence: 99%
“…The surveys were developed to measure the experiences and expectations of youth with disabilities as they transition to adulthood. Based on previous research (Powers et al, 2005), the following themes were identified: postschool activities cited in the IDEA (i.e., independent living, community participation, postsecondary education), self-determination skills, barriers and sources of support for transition, and gender equity. Multiple items for each of these themes were developed.…”
Section: Instrumentation and Data Analysismentioning
confidence: 99%
“…Of course, other factors beyond the scope of this research may also have contributed to this lack of planning. These results were similar to those found by Powers et al (2005) who found a lack of transition goals for special education students from school districts in the Western U.S. (only 63% with employment goals, 50.4% with postsecondary goals, and fewer than half with independent living goals). Differences between desired goals and jobs obtained may also have been affected by the over-estimation of ability by students with mild disabilities (Klassen, 1992).…”
Section: Analysis Rq1supporting
confidence: 89%
“…Limitations for the K. M. Powers et al (2005) The authors suggested that more research is needed to confirm this finding. Many work experiences are overly narrow and are not individualized to students' interests.…”
Section: Transition Components In the Iepmentioning
confidence: 95%
“…Current research has characterized transition goals as vague and overly broad, suggesting limited connections between young adults' unique characteristics and the post school goals identified in their transition plans (Powers et al, 2005;Trainor, 2005b). Moreover, disparities in transition goals have been identified across different ethnic groups.…”
Section: Adaptations For Goal Settingmentioning
confidence: 99%